2022
DOI: 10.1101/2022.06.27.497875
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Combination therapy with nirmatrelvir and molnupiravir improves the survival of SARS-CoV-2 infected mice

Abstract: As the SARS-CoV-2 pandemic remains uncontrolled owing to the continuous emergence of variants of concern, there is an immediate need to implement the most effective antiviral treatment strategies, especially for risk groups. Here, we evaluated the therapeutic potency of nirmatrelvir, remdesivir, and molnupiravir and their combinations in SARS-CoV-2-infected K18-hACE2 transgenic mice. Systemic treatment of mice with each drug (20 mg/kg) resulted in slightly enhanced antiviral efficacy and yielded an increased l… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 50 publications
3
5
0
Order By: Relevance
“…As the mode of action for MK-4482 and PF-07321332 are distinct, the former being a nucleoside analog and the latter an inhibitor of viral protease inhibitor, combined therapy may provide a potential benefit over monotherapy. This was supported by recent in vitro data demonstrating a synergistic antiviral effect of MK-4482 and PF-07321332 against Delta and Omicron VOCs in comparison to individual drug treatment [27,28], and in vivo for a Korean strain isolated early in the pandemic [29] using a transgenic mouse model [30]. In our present study, combined twice daily oral treatment (1600mg in total) within 5 days of symptom onset [31].…”
Section: Treated Animals Had Less Pathology and Viral Antigen In The ...supporting
confidence: 83%
See 1 more Smart Citation
“…As the mode of action for MK-4482 and PF-07321332 are distinct, the former being a nucleoside analog and the latter an inhibitor of viral protease inhibitor, combined therapy may provide a potential benefit over monotherapy. This was supported by recent in vitro data demonstrating a synergistic antiviral effect of MK-4482 and PF-07321332 against Delta and Omicron VOCs in comparison to individual drug treatment [27,28], and in vivo for a Korean strain isolated early in the pandemic [29] using a transgenic mouse model [30]. In our present study, combined twice daily oral treatment (1600mg in total) within 5 days of symptom onset [31].…”
Section: Treated Animals Had Less Pathology and Viral Antigen In The ...supporting
confidence: 83%
“…Since SARS-CoV-2 Delta infection likely shows the most severe infection in a NHP model [26], this could be addressed in lethal rodent models or clinical trials. A suggestion of such efficacy against more severe disease is indicated in the recent study using a lethal transgenic COVID-19 mouse model [30]. Second, we only tested the efficacy of the current human dose for monotherapy.…”
Section: Treated Animals Had Less Pathology and Viral Antigen In The ...mentioning
confidence: 99%
“…Another study showed synergistic inhibition of viral replication by Paxlovid and molnupiravir in vitro [7]. Synergy was also seen with these two agents in a murine model of survival after infection with the SARS-CoV-2 Beta variant [8]. One other case report exists which corroborates our experience with dual DAAs [9].…”
Section: Introductionsupporting
confidence: 79%
“…Preclinical data have clearly demonstrated that virological efficacy is higher for combinations of existing antiviral drugs than single agents (Abdelnabi et al, 2021 ; Jeong et al, 2022 ; Li et al, 2022 ). To achieve the goal of changing the treatment guidelines in SARS-CoV-2-infected immunocompromised individuals, independent and academic clinical trials for drug combinations should be considered as an urgent, unmet research priority.…”
Section: Protecting Emerging Treatment Optionsmentioning
confidence: 99%
“…With few drugs currently available, the opportunity must be seized prior to the emergence of resistance to drugs deployed widely as monotherapies. Combinations of polymerase inhibitors and polymerase/protease inhibitors have proven highly successful for other viruses and in animal models for SARS-CoV-2 (Abdelnabi et al, 2021 ; Jeong et al, 2022 ). Thus, as drugs that are appropriate to combine are available, there is no good reason not to study them clinically.…”
Section: Expert Opinionmentioning
confidence: 99%